Acute myeloid leukemia in the elderly: do we know who should be treated and how?. Issue 5 (May 2014) - Nazha, Aziz; Ravandi, Farhad
Abstract Acute myeloid leukemia (AML) in the elderly is associated with several distinctive biological and clinical features compared to younger patients. Despite the advances in supportive care and the introduction of less intensive chemotherapy regimens, the overall outcome for this population remains poor. More importantly, the decision making process for choosing the appropriate treatment for individual patients, based on their comorbidities and the biological features of their disease, continues to be challenging for treating physicians. Currently, a significant number of elderly patients with AML do not receive treatment above and beyond supportive care; several studies have suggested that patients who receive any therapy have a better outcome than patients who receive palliation alone. Furthermore, the development of novel, targeted and less intensive therapies is providing new options suitable for older patients with multiple comorbidities and with high risk disease features. In this review, we highlight the challenges that face treating physicians when encountering elderly patients with AML and describe some of the potential strategies under development for treating older patients with AML and the available data from recent clinical trials.